2009
DOI: 10.1007/s10103-009-0652-9
|View full text |Cite
|
Sign up to set email alerts
|

Acid-etch interval and shear bond strength of Er,Cr:YSGG laser-prepared enamel and dentin

Abstract: The formation of a superficial layer of tiny flakes has been observed on teeth prepared by Erbium lasers. It has been suggested that removing this layer (mechanically or chemically) may increase the bond strength of the resin composite. The purpose of this study is to evaluate the effect of various etching times on bond strength of resin composite to enamel and dentin prepared by Er,Cr:YSGG laser. Sixty previously flattened human molars were irradiated for 10 s by an Er,Cr:YSGG laser. Enamel (E) specimens were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 29 publications
1
38
0
4
Order By: Relevance
“…The output power of Er,Cr:YSGG laser can vary from 0 to 6 W [37]. Various output values were evaluated for dental use ranging from 0.5 to 1 W, 3 to 4.5 W and 6 W [38,39]. In the present study, high output values were tested since the laser was applied to the post surfaces that were not in contact with dental tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The output power of Er,Cr:YSGG laser can vary from 0 to 6 W [37]. Various output values were evaluated for dental use ranging from 0.5 to 1 W, 3 to 4.5 W and 6 W [38,39]. In the present study, high output values were tested since the laser was applied to the post surfaces that were not in contact with dental tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies 16,29,30) evaluating the influence of acid etching time on bond strength in dentin irradiated with Er,Cr:YSGG lasers used the etching time of 15 sec, the conventional etching time of dentin and 30 sec with 37% phosphoric acid. And the laser output of 3 W or 4 W was used in those studies, which was much higher than used in current study (0.25 W).…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…To overcome this problem, mechanical or chemical removing of laser-modified layer has been suggested [14][15][16] . Gutknrcht et al 14) and Carvalho et al 15) suggested additional acid-etching of the laser-prepared cavity.…”
Section: ⅰ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has a 2780-nm wavelength and absorbed strongly by both water and hydroxyapatite. The sudden evaporation of bound water causes micro-explosions that blast away tiny particles of the tooth (Obeidi et al, 2010). Previous studies reported that irregularities and the crater-shaped appearance of ablated dentin was comparable to the dentine surface after acid etching, which might promote micromechanical interlocking between dental restorative materials and the tooth surface (Visuri et al, 1996;Armengol et al, 1999;Martínez-Insua et al, 2000;Carrieri et al, 2007;Gurgan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%